2013
DOI: 10.1517/14728214.2013.802305
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs for the treatment of diabetic ulcers

Abstract: Introduction Diabetic ulcers are chronic non-healing ulcerations that despite the available medical tools still result in high amputation rates. Growing evidence suggests that alteration of the biochemical milieu of the chronic wound plays a significant role in diabetic wound healing impairment. Areas covered The basic pathophysiology and the conventional treatment strategy of diabetic foot ulcers have been reviewed in the first section. In the second part we describe the most up-to-date bench and translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 98 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…Kusmanto et al conducted a double-blind study where the efficacy of VEGF was compared against a placebo. The study reported a more significant DFU reduction (60%) in patients treated with VEGF than in those treated with placebo [52]. After VEGF, FGFb shows the most potent mitogenic activity.…”
Section: Growth Factorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Kusmanto et al conducted a double-blind study where the efficacy of VEGF was compared against a placebo. The study reported a more significant DFU reduction (60%) in patients treated with VEGF than in those treated with placebo [52]. After VEGF, FGFb shows the most potent mitogenic activity.…”
Section: Growth Factorsmentioning
confidence: 88%
“…There is currently insufficient data regarding their efficacy, and they are not widely available. Some of these factors are combined with different extracts and molecules to yield a synergy of activity [52]. PDGF-BB is the most widely studied growth factor in wound healing and is currently approved for clinical use in recombinant DNA technology [53].…”
Section: Growth Factorsmentioning
confidence: 99%
“…Despite the many modern alternative methods, sharp debridement using scalpel and scissors is still regarded as the benchmark care for DFUs and plays a vital role in wound control by effectively removing relevant biofilm. 35 Recently, larval therapy is used for chronic, non-healing wounds, particularly in diabetic patients. The mechanism of therapy consists of debridement and disinfection of chronic wounds and wound healing promotion through maggot secretions and excretions against gram-positive and gram-negative bacteria.…”
Section: Current Non-surgical Treatment Options For Dfusmentioning
confidence: 99%
“…Therefore, infection control in chronic wounds, particularly those infected with antibiotic-resistant bacteria, is a major management concern (Apelqvist and Larsson, 2000;Falanga, 2004;Robson, 1997). To date, several medications have been developed for treatment of chronic pressure ulcers and diabetic wounds, but most of them have proven ineffective, except for PDGF (Shah et al, 2012;Tecilazich et al, 2013). However, it has been reported that PDGF increases the risk for cancer development and is ineffective for chronic wounds (Ma et al, 2015;Park et al, 2014;Tecilazich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several medications have been developed for treatment of chronic pressure ulcers and diabetic wounds, but most of them have proven ineffective, except for PDGF (Shah et al, 2012;Tecilazich et al, 2013). However, it has been reported that PDGF increases the risk for cancer development and is ineffective for chronic wounds (Ma et al, 2015;Park et al, 2014;Tecilazich et al, 2013). Therefore, new medicines for chronic nonhealing wounds are needed.…”
Section: Introductionmentioning
confidence: 99%